1988
DOI: 10.1017/s0021859600081326
|View full text |Cite
|
Sign up to set email alerts
|

Growth and dry-matter partitioning in sugar beet

Abstract: SummaryData from 11 sugar-beet crops grown at different sites, in different years and with some variations in husbandry have been used to re-examine the process of dry-matter partitioning. Two-phase linear models did not describe adequately the distribution of dry matter. There was no evidence of a discontinuity in the partitioning between root and shoot at any point in crop development. It is suggested that, contrary to a recent view, events in the shoot, rather than the storage root, largely determine how dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 20 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…7 Change in Sugar Yield relative to total dry matter during the growing season IV DISCUSSION As shown in Fig. 2, in the early stages of growth, the accumulation of dry weight is slow because of the distance between plants, the slow growth of small leaves and consequently, the limitation of light absorption (8). After this stage, with the completion of leaf cover, there is a direct relation between the production of dry matter and the amount of light received (3,9).…”
Section: Fig 5 Sugar Beet Root To Shoot Dry Matter Ratio During the mentioning
confidence: 97%
See 2 more Smart Citations
“…7 Change in Sugar Yield relative to total dry matter during the growing season IV DISCUSSION As shown in Fig. 2, in the early stages of growth, the accumulation of dry weight is slow because of the distance between plants, the slow growth of small leaves and consequently, the limitation of light absorption (8). After this stage, with the completion of leaf cover, there is a direct relation between the production of dry matter and the amount of light received (3,9).…”
Section: Fig 5 Sugar Beet Root To Shoot Dry Matter Ratio During the mentioning
confidence: 97%
“…On this basis, it is expected that the rapid root growth takes place in a short time period or at a certain stage of the plant growth period. However, some other reports indicate that, as plant growth, a gradual phase change occurs in the allocation of dry matter to the root, and no sudden transition occurs at a definite stage (8,16).…”
Section: Fig 5 Sugar Beet Root To Shoot Dry Matter Ratio During the mentioning
confidence: 99%
See 1 more Smart Citation
“…During the early growth stages, 15% to 40% of the daily dry matter produced is partitioned into root. After the full canopy development, 85% of the daily dry matter produced is partitioned into root tuber formation (Milford et al, 1988;Leviel, 2000). Final marketable sugarbeet yield is computed from total root dry matter, assuming that 95% of the root is harvested and that roots have 82% moisture content (Leviel, 2000).…”
Section: Rzwqm and Csm-ceres-beetmentioning
confidence: 99%
“…Excess N fertilizer results in larger total DM accumulation, but lower total gross and extractable sucrose yields, and could lead to losses of N to the environment. Milford et al (1988), Armstrong and Milford (1983), and Hills et al (1983) all reported that beets require lower levels of N than many other crops for maximum sugar yields and that sugar beet can serve as a nitrogen-scavenging crop to prevent possible nitrate pollution of groundwater. N fertilizer use has tended to decline with increasing yields.…”
Section: Sugar Beet Growth and Managementmentioning
confidence: 99%